The last Karankawas - Garza, Kimberly, 1985- (Henry Holt and Company, 2022)
"A kaleidoscopic, emotionally charged debut about a tight-knit community of Mexican and Filipino families on the Texas coast. Unflinching, lyrical, and singular, The Last Karankawas is a portrait of America rarely witnessed, where browning palm trees and oily waters mark the forefront of ecological change. It is a deeply imagined exploration of familial inheritance, human perseverance, and the histories we assign to ourselves, establishing Kimberly Garza as a brilliant new literary voice"--